Fetomaternal Outcome of Instrumental Vaginal Delivery at Nepalgunj Medical College Teaching Hospital Kohalpur - BC, Durga; Jha, Rajshree; Das, Ram Kumar (Journal of Nepalgunj Medical College, 2022)
Introduction: Instrumental vaginal delivery is performed in second stage of labor to expedite delivery with aim to decrease cesarean section rate. Worldwide 10-20% of laboring women need obstetrics intervention for delivery. Aims: To evaluate the indication and fetomaternal outcome of instrumental vaginal delivery. Methods: This is a hospital based cross-sectional study conducted at the department of obstetrics and gynecology. The study was done from July 2021 to July 2022 for a period of one year. Data were collected, recorded in standard proforma and analyzed by using SPPS version 20. Results: The out of 6123 deliveries, 149(2.4%) had instrumental vaginal delivery. Out of 149 participants, 41.6% were between 20-24 years, 10.7% were of age group 15-19 years and 4% ladies were of >35 years. Instrument delivery was more frequently applied in primigravida in comparison to multigravida (57.3% vs 42.3%) p=0.046. The most common indication for instrumentation was poor maternal effort (41%) followed by fetal distress (33.6%). About 14.1% had postpartum haemorrhage, 3.4% had vulval hematoma, and 38.3% babies had Neonatal Intensive Care unit admission. Conclusion: Poor maternal effort and fetal distress were the common indications for instrumental delivery with some fetomaternal complications. Inspite of the complications, if used by an expertise, instrumental delivery can reduce the need of cesarean section.